THE EMERGENCE OF ANCIENT WRITING CULTURE AND ARCHIVAL WORK IN CENTRAL ASIA - Samadqulova, Gulzoda (Journal of Contemporary World Studies, 2024)
To provide information on the emergence of signs of writing in Central Asia, stages of formation of writing culture, the emergence of the Aramaic script, Parthian, khwarezmian, sugary, Aramaic-bokhtarian, Greco-bokhtar, Arabic scripts.